Direct deposition of Sn-doped CsPbBr3 perovskite for efficient solar cell application. Issue 6 (15th January 2021) - Abib, Mukerem Helil; Li, Junchun; Yang, Heming; Wang, Man; Chen, Taotao; EnzeXu; Jiang, Yang
Abstract : All inorganic carbon-based planar perovskites, particularly CsPbBr3, have attracted considerable attention due to their excellent stability against oxygen, moisture, and heat for photovoltaic utilization. Abstract : All inorganic carbon-based planar perovskites, particularly CsPbBr3, have attracted considerable attention due to their excellent stability against oxygen, moisture, and heat for photovoltaic utilization. However, the power conversion efficiency of carbon-based planar CsPbBr3 perovskite solar cells is mostly low, primarily because of the inferior film quality with undesirable crystallization and narrow light absorbance ranges. Herein, we develop a novel direct deposition approach combined with Sn doping to achieve highly efficient and stable carbon-based Sn-doped CsPbBr3 perovskite solar cells. Mass-scale Sn ion-doped CsPbBr3 perovskite powder was effectively synthesized and characterized via a facile strategy by adding hydrohalic acid in the CsBr, PbBr2 and SnBr2 precursor in a dimethyl sulfoxide solution. Moreover, using the as-synthesized CsPbBr3 and Sn-doped CsPbBr3 perovskite powder, PSCs were obtained via effective direct thermal evaporation. A smooth, constant and pinhole-free perovskite film was achieved with a configuration of FTO/TiO2 /Sn:CsPbBr3 /carbon. PSCs based on Sn:CsPbBr3 as an absorber and carbon as the HTM achieved an impressive power conversion efficiency of 8.95% compared to 6.87% for undoped CsPbBr3 ; moreover, it displayed admirable stability in an open-air atmosphere for an operational period of about 720 h without a noticeable negative result. The introduction of the Sn ion may advance the interface extraction of charge between the electric transport layer to the absorber layer and absorber to the carbon electrode. Accordingly, the Sn ion doping on CsPbBr3 during the synthesis phase and the direct evaporation paves a novel approach for intended photovoltaic applications.